2020
DOI: 10.1093/auk/ukaa002
|View full text |Cite
|
Sign up to set email alerts
|

Local conspecific density does not influence reproductive output in a secondary cavity-nesting songbird

Abstract: Density dependence is a conceptual cornerstone of avian population biology and, in territorial songbirds, past research has emphasized interactions among food limitation, density, and reproduction. Documenting the importance of density effects is central to understanding how selective forces shape life histories and population dynamics. During the 2008–2011 breeding seasons, we nearly doubled overall conspecific breeding densities on study sites, and manipulated nest box spacing to increase local breeding dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 78 publications
3
9
0
Order By: Relevance
“…The likely reason for this is that earlier breeding associated with warmer temperatures resulted in an increased probability of fledging two broods within a given breeding season. An increase in attempting second broods previously had been documented in our study system (Hoover et al, 2020), as well as in a study of prothonotary warblers in Virginia, United States (Bulluck et al, 2013). Similar patterns of increased double brooding, or increased chances of successfully producing a replacement brood, as a byproduct of nesting earlier in warmer years has also been found in other species (Halupka et al, 2008;Monroe et al, 2008;Verhulst and Nilsson, 2008;Townsend et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The likely reason for this is that earlier breeding associated with warmer temperatures resulted in an increased probability of fledging two broods within a given breeding season. An increase in attempting second broods previously had been documented in our study system (Hoover et al, 2020), as well as in a study of prothonotary warblers in Virginia, United States (Bulluck et al, 2013). Similar patterns of increased double brooding, or increased chances of successfully producing a replacement brood, as a byproduct of nesting earlier in warmer years has also been found in other species (Halupka et al, 2008;Monroe et al, 2008;Verhulst and Nilsson, 2008;Townsend et al, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Previous research in our study system demonstrated that females that nest earlier are more likely to attempt second broods (Hoover et al, 2020). Thus, local warmer April temperatures could also increase the probability of females successfully fledging two broods and explain any increases in productivity we observed.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations